Effect of nisin on the keeping quality of Dahi - Sreeja Ramachandran (Department of Dairy Science, College of Veterinary and Animal Sciences, 1992)
An experiment was conducted to find out the effect of preservatives such as nisin and potassium sorbate on the keeping quality of dahi. An attempt was also made to study the quality of dahi produced under household conditions with a special emphasis on the maintenance of starter.